A Presentation of the Paideia Omogenon Program - Kontoyiannis, Dionyssia (Études helléniques / Hellenic Studies, 2005)
This article provides the legal, historical and pedagogical background to the Paideia Omogenon Program of the Greek Government. The author outlines in detail the philosophy and application of the program in the diaspora, from material design and field testing to teacher training, building on the realities of the Greek diaspora. She concludes with results gathered after seven years of the program’s existence.